A quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell

CN116367565BActive Publication Date: 2026-10-20HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310042995.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-28
Publication Date
2026-10-20
Estimated Expiration
2043-01-28

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对目前钙钛矿电池普遍存在的钙钛矿缺陷较多,性能较差造成其难以走向实际应用的问题,提出了一种准二维钙钛矿纳米晶修饰三维钙钛矿太阳能电池

Benefits of technology

[0030]经过研究发现,钙钛矿太阳能电池中的钙钛矿吸光层表界面处存在大量缺陷,对电池性能有着极大的负面影响。当前技术中,仅用零维钙钛矿纳米晶来钝化三维钙钛矿表面缺陷,但零维钙钛矿纳米晶清洗次数少时,表面会存在大量配体,在修饰三维钙钛矿后会对载流子传输产生负面影响,降低器件的电流密度。而当清洗次数过多时,纳米晶容易发生团聚,且暴露出来大量的表面缺陷,不仅会使得纳米晶的稳定性降低,对器件的性能也存在一定危害。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116367565B_ABST
    Figure CN116367565B_ABST
Patent Text Reader

Abstract

The application discloses a quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell. The solar cell comprises a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light absorption layer, a quasi-two-dimensional perovskite nanocrystal layer, a hole transport layer and an electrode. The three-dimensional perovskite light absorption layer material is APbX3, and the quasi-two-dimensional perovskite nanocrystal has a structural formula of (B2PbX4) k (A2PbX4) m (APbX3) n wherein B is a macromolecular organic halide amine salt cation. The application has the advantages of simple preparation process, high efficiency and low cost. The three-dimensional perovskite / quasi-two-dimensional perovskite nanocrystal thin film obtained by the application has high quality, low defect density, improved carrier extraction and transport capacity, excellent intrinsic stability and excellent photoelectric conversion efficiency, and has a good application prospect in the field of photovoltaic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel semiconductor optoelectronic materials and devices, specifically relating to a quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell. Background Technology

[0002] Currently, the energy used by humankind is mainly based on fossil fuels, but their limited reserves cannot meet the ever-increasing demand, and the combustion products also contribute to global climate deterioration. Compared with traditional energy sources, solar energy has become a focus of research due to its wide availability, renewability, and environmental friendliness. Among photovoltaic materials, organic-inorganic hybrid perovskite materials have attracted much attention due to their excellent photoelectric properties, such as high light absorption coefficient, high carrier migration characteristics, and tunable bandgap. The photoelectric conversion efficiency of perovskite solar cells was only 3.8% in 2009, but it has exceeded 25% in just over a decade of development, very close to that of silicon-based solar cells, which have been developed for decades. It is a new type of solar cell that combines low processing costs, high photoelectric conversion efficiency, and broad development prospects, and has great commercial potential.

[0003] However, during device fabrication, numerous defects exist at perovskite grain boundaries and surfaces, leading to nonradiative recombination. This affects carrier transport performance and reduces carrier lifetime, severely impacting the efficiency and stability of perovskite solar cells. Therefore, reducing defects at perovskite grain boundaries and surfaces, minimizing nonradiative recombination, optimizing energy level alignment, and improving carrier mobility and lifetime are essential factors for further enhancing the photoelectric conversion efficiency and stability of perovskite solar cells. These are crucial for achieving high-efficiency, stable, and hysteresis-free perovskite solar cells (PSCs).

[0004] In recent years, zero-dimensional perovskite nanocrystals have been widely used in solar cells, LED displays, and photodetectors due to their flexible and variable composition, adjustable band gap, excellent stability, and high carrier transport capacity. Patent CN109360893A uses zero-dimensional CsPbX3 (X = Cl, Br, I, or mixtures thereof) nanocrystals to modify perovskite films. The method involves spin-coating zero-dimensional CsPbX3 nanocrystals onto the surface of a three-dimensional perovskite film and passivating surface vacancy defects through solid-state diffusion, thereby reducing defect density and improving the photoelectric conversion efficiency and long-term stability of the battery. However, the zero-dimensional perovskite nanocrystals used in this method have a large number of long carbon chain ligands on their surface, which affects carrier transport capacity and reduces the current density of the device. Simultaneously, the surface also contains numerous defects, resulting in poor stability. Therefore, the performance improvement obtained by devices fabricated using these nanocrystals to modify three-dimensional perovskites is limited. Summary of the Invention

[0005] The purpose of this invention is to address the problem of poor performance and numerous defects in perovskite solar cells, which hinders their practical application. This invention proposes a quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell. This invention utilizes quasi-two-dimensional RP-phase perovskite nanocrystals formed through an in-situ reaction to modify the surface defects of three-dimensional perovskite. Starting with the interaction between zero-dimensional perovskite nanocrystals and macromolecular organic halide amine salts, zero-dimensional perovskite nanocrystals are first used to modify the three-dimensional perovskite. Then, macromolecular organic halide amine salts are used to segment the zero-dimensional nanocrystals and react them to generate quasi-two-dimensional perovskite nanocrystals, thus forming a three-dimensional perovskite / quasi-two-dimensional perovskite nanocrystal structure solar cell. The fabrication process of this invention is simple, efficient, and low-cost. The resulting three-dimensional perovskite / quasi-two-dimensional perovskite nanocrystal thin film exhibits improved quality, reduced defect density, decreased non-radiative recombination, and significantly improved carrier extraction and transport capabilities. It possesses excellent intrinsic stability and superior photoelectric conversion efficiency, showing promising application prospects in the photovoltaic device field.

[0006] The technical solution of this invention is as follows:

[0007] A quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell includes a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light-absorbing layer, a quasi-two-dimensional perovskite nanocrystal layer, a hole transport layer, and electrodes.

[0008] The three-dimensional perovskite light-absorbing layer material is APbX3, where A is a formamidinium cation (FA). + ), methylamine cation (MA) + ) and cesium ions (Cs + One or more of the following; the X position is a chloride ion (Cl... - ), bromide ions (Br) - ), iodide ions (I) - One or more of the following.

[0009] The quasi-two-dimensional perovskite nanocrystal structure has the formula (B2PbX4). k (A2PbX4) m (APbX3) n Where k is 0 to 1, m and n are 0 to 20, A is a monovalent cation, B is a macromolecular organic halide amine salt cation, and X is one or more of a monovalent halogen or pseudohalogen anion.

[0010] The macromolecular organic halide amine salt cation B is specifically: methoxyphenethylamine ion (MeO-PEA). + ), phenylethylamine ion (PEA) + pF-PEA ions + ), dimethylamine ion (DMA) + ), ethylamine ion (EA)+ ), diethylamine ion (DEA) + ), mercaptoethylamine ion (ESA) + ), ethanolamine ions (EOA) + ), propylamine ion (PA) + ), butylamine ion (BA + ), isobutylamine ion (iBA) + ), phenylamine ion (PhA) + ), pyridine methylamine ion (PyA) + ), trifluoroethylamine ion (F3-EA) + ), trifluoromethylphenylethylamine ion (CF3-PEA) + ), trifluoromethylaniline ion (CF3-PhA) + ), trifluoromethylbenzamine ion (CF3-PMA) + ), 3-Dimethylamino-1-propylamine ion (3-Me2-PDA) + ), benzylamine ion (PMA) + ), phenylpropylamine ion (PPA) + ), phenylbutylamine ion (PhBA) + p-fluorobenzamide ions (pF-PMA) + ), 4-tert-butylbenzylamine ion (tBBA) + ), 4-tert-butylaniline ion (tBPA) + One or more of the following.

[0011] The substrate is one of the following: fluorine-doped SnO2 conductive glass (FTO), indium tin oxide transparent conductive film glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate).

[0012] The electrode is at least one of gold, silver, copper, aluminum, and carbon.

[0013] The electron transport layer includes at least one of tin dioxide, titanium dioxide, zinc oxide, methyl [6,6]-phenyl C61 butyrate (PCBM), and C60.

[0014] The hole transport layer is composed of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), molybdenum trioxide (MoO3), and nickel oxide (NiO). x One or more of the following: cuprous iodide (CuI), cuprous thiocyanate (CuSCN), copper titanate (CuPc), and chromium oxide (Cr2O3).

[0015] The thickness of the three-dimensional perovskite is 200-1000 nm, the thickness of the quasi-two-dimensional perovskite nanocrystals is 0.1-100 nm, the thickness of the electron transport layer is 1-200 nm, the thickness of the hole transport layer is 5-300 nm, and the thickness of the electrode is 20-500 nm.

[0016] The method for preparing the quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell includes the following steps:

[0017] 1) An electron transport layer is fabricated on a cleaned transparent conductive substrate;

[0018] 2) Fabrication of a three-dimensional perovskite layer on the electron transport layer;

[0019] 3) Preparation of quasi-two-dimensional perovskite nanocrystal layer: Zero-dimensional perovskite nanocrystal colloid is spin-coated onto three-dimensional perovskite and annealed at 20-150℃ for 30s-20min; then, a layer of macromolecular organic halide amine salt solution is spin-coated and annealed at 20-150℃ for 30s-20min.

[0020] The concentration of the zero-dimensional perovskite nanocrystal colloid is 0.1–20 mg / mL; the concentration of the macromolecular organic halide amine salt solution is 0.1–20 mg / mL, and the solvent is isopropanol.

[0021] The macromolecular organohalogenated amine salts mentioned are: methoxyphenylethyl iodide (MeOPEAI), phenylethyl iodide (PEAI), p-fluorophenylethylamine iodide (pF-PEAI), dimethylamine hydroiodide (DMAI), ethyl iodide (EAI), diethylamine hydroiodide (DEAI), mercaptoethylamine hydroiodide (ESAI), ethanolamine iodide (EOAI), propylamine iodide (PAI), butylamine iodide (BAI), isobutylamine iodide (iBAI), phenylamine iodide (PhAI), pyridine methylamine iodide (PyAI), trifluoroacetyl iodide, etc. One or more of the following: aminoiodine (F3-EAI), trifluoromethylphenethylamine iodine (CF3-PEAI), trifluoromethylaniline iodine (CF3-PhAI), trifluoromethylaniline iodine (CF3-PMAI), 3-dimethylamino-1-propylamine iodine (3-Me2-PDAI), benzyl iodide (PMAI), phenylpropyl iodide (PPAI), phenylbutyl iodide (PhBAI), p-fluoroaniline iodine (pF-PMAI), 4-tert-butylaniline iodine (tBBAI), and 4-tert-butylaniline iodine (tBPAI);

[0022] 4) Spin-coat hole transport material onto the perovskite layer at a concentration of 1–100 mg / mL;

[0023] 5) Prepare metal electrodes on the hole transport layer by vacuum evaporation or carbon electrodes by blade coating.

[0024] The preparation of the three-dimensional perovskite thin film in step 2) is carried out by one of the following two methods:

[0025] Method 1: A three-dimensional perovskite light-absorbing layer is prepared by vacuum flash evaporation at an ambient temperature of 1–50℃ and a relative humidity of 2%–60%. A prepared perovskite precursor solution with a concentration of 0.5–2 mol / L is spin-coated onto the electron transport layer at a spin coating speed of 1000–6000 rpm for 5–60 s. Then, a low-pressure assisted treatment is performed at a pressure of 1–200 Pa for 10–120 s, followed by annealing at a temperature of 50–150℃ for 30 s–50 min to form the three-dimensional perovskite layer.

[0026] Alternatively, in method two, a three-dimensional perovskite light-absorbing layer is prepared by a one-step spin coating method at an ambient temperature of 1–50℃ and an ambient relative humidity of 2%–60%. A prepared perovskite precursor solution with a concentration of 0.5–2 mol / L is spin-coated onto the electron transport layer. The spin coating equipment is operated at a speed of 1000–6000 rpm for 5–60 s. An anti-solvent is added dropwise during the spin coating process, followed by annealing at a temperature of 50–150℃ for 30 s–50 min to form a three-dimensional perovskite layer.

[0027] The solvent of the perovskite mixed solution includes one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile (ACN), dimethylacetamide (DMAc), γ-butyrolactone, methylamine formate, methylamine acetate, methylamine butyrate, and methanol.

[0028] Step 3) The rotation speed of the spin coating equipment is 500-6000 rpm, the rotation time is 5-120 s, the ambient temperature is 1-50℃, and the ambient relative humidity is 2%-60%.

[0029] The essential features of this invention are:

[0030] Research has revealed numerous defects at the interface of the perovskite light-absorbing layer in perovskite solar cells, significantly impacting cell performance. Current technology uses only zero-dimensional perovskite nanocrystals to passivate surface defects in three-dimensional perovskites. However, with insufficient cleaning cycles, the nanocrystals accumulate numerous ligands on their surface, negatively affecting carrier transport and reducing current density after modification of the three-dimensional perovskite. Conversely, excessive cleaning cycles lead to nanocrystal aggregation and expose numerous surface defects, reducing nanocrystal stability and jeopardizing device performance.

[0031] This invention eliminates the need for a complex process of first preparing quasi-two-dimensional perovskite nanocrystals and then modifying them with three-dimensional perovskites. Instead, it directly modifies the structure of zero-dimensional perovskite nanocrystals by adding macromolecular organic halide amine salts. The resulting quasi-two-dimensional perovskite nanocrystals, due to their structural characteristics, are more conducive to the longitudinal transport of charge carriers, thus giving the device superior photoelectric performance. Furthermore, the application of such quasi-two-dimensional perovskite nanocrystals in the field of solar cells has not yet been explored.

[0032] Compared to zero-dimensional perovskite nanocrystals, quasi-two-dimensional perovskite nanocrystals exhibit higher stability, longer carrier lifetime, lower defect state density, and faster carrier transport. Therefore, this invention employs quasi-two-dimensional RP-phase perovskite nanocrystals to modify the surface of three-dimensional perovskites, thereby improving the overall performance of perovskite solar cells.

[0033] The beneficial effects of this invention are as follows:

[0034] The quasi-two-dimensional perovskite nanocrystals described in this invention passivate surface defects in three-dimensional perovskites. This not only passivates surface vacancy defects through solid-state diffusion but also optimizes interface contact, improves energy level matching, reduces non-radiative recombination, and suppresses perovskite degradation and phase transitions through lattice stress. Compared to unmodified devices, devices modified with quasi-two-dimensional perovskite nanocrystals exhibit an open-circuit voltage increase from 1.08V to 1.14V, and a fill factor increase from 77.4% to 79.8%. Furthermore, the introduced macromolecular organic halide amine salt cations enhance the hydrophobic properties of the perovskite, suppress ion migration, and improve device stability. In addition, the horizontally and vertically arranged quasi-two-dimensional perovskite nanocrystals effectively mitigate the carrier transport obstruction caused by the horizontal arrangement of organic molecules in traditional two-dimensional / three-dimensional devices, significantly improving carrier transport capacity. This results in a current density increase from 25.52 mA / cm² in devices modified with quasi-two-dimensional perovskite nanocrystals. 2 It was increased to 25.57 mA / cm 2 From the perspective of device efficiency, the photoelectric conversion efficiency of the unmodified three-dimensional perovskite device and the three-dimensional perovskite device modified with zero-dimensional perovskite nanocrystals are 21.33% and 22.52%, respectively, while the photoelectric conversion efficiency of the three-dimensional perovskite device modified with quasi-two-dimensional perovskite nanocrystals reaches 23.26%, showing a significant improvement in performance. Attached Figure Description

[0035] Figure 1 This is a schematic diagram of the perovskite solar cell structure described in this invention;

[0036] Figure 2 Transmission electron microscopy image of the zero-dimensional CsPbBr3 nanocrystals in Example 1;

[0037] Figure 3 This is a high-resolution transmission electron microscopy image of the zero-dimensional CsPbBr3 nanocrystals in Example 1.

[0038] Figure 4 Transmission electron microscopy image of the quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystals in Example 1;

[0039] Figure 5 High-resolution transmission electron microscopy image of the quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystals in Example 1;

[0040] Figure 6 The three-dimensional FA prepared in Example 1 0.85 MA 0.15Scanning electron microscopy image of the surface of PbI3 perovskite thin film;

[0041] Figure 7 The three-dimensional FA prepared in Example 1 0.85 MA 0.15 Scanning electron microscopy image of the surface of PbI3 / zero-dimensional CsPbBr3 nanocrystalline perovskite film;

[0042] Figure 8 The three-dimensional FA prepared in Example 1 0.85 MA 0.15 Scanning electron microscopy image of the surface of PbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite thin film;

[0043] Figure 9 For the three-dimensional FA in Comparative Example 1 0.85 MA 0.15 JV curve of solar cells prepared from PbI3 perovskite;

[0044] Figure 10 For the three-dimensional FA in Comparative Example 2 0.85 MA 0.15 JV curve of solar cells fabricated from PbI3 / zero-dimensional CsPbBr3 nanocrystalline perovskite;

[0045] Figure 11 The three-dimensional FA in Example 1 0.85 MA 0.15 JV curve of solar cells prepared from PbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite; Detailed Implementation

[0046] The following embodiments are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention to the scope of the embodiments described.

[0047] Example 1.

[0048] Based on 3D FA 0.85 MA 0.15 A perovskite solar cell with a PbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layer is shown in the schematic diagram below. Figure 1 As shown, from bottom to top, the structure consists of a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light-absorbing layer, a quasi-two-dimensional perovskite nanocrystal layer, a hole transport layer, and electrodes. The specific fabrication process is as follows:

[0049] Step 1: Clean the FTO substrate:

[0050] The FTO substrate was ultrasonically cleaned for 15 minutes each with glass cleaner, deionized water, and anhydrous ethanol, and the surface liquid was dried with a nitrogen gun. The size of the FTO substrate was 20×20mm.

[0051] Step 2: Preparation of the electron transport layer TiO2:

[0052] Prepare TiO2 growth solution: Dissolve 2 mL of titanium tetrachloride liquid (TiCl4) in a blue-mouthed bottle containing 100 mL of deionized water, refrigerate, and set aside for later use.

[0053] The FTO substrate was immersed in a staining dish containing TiO2 growth solution and placed in an oven at 70°C for 2 hours. After that, it was removed and ultrasonically cleaned with deionized water for 5 minutes. The surface liquid was dried with nitrogen gas and then annealed at 150°C for 60 minutes to obtain the TiO2 electron transport layer.

[0054] Step 3: Preparation of three-dimensional FA 0.85 MA 0.15 PbI3 perovskite light-absorbing layer:

[0055] Configure 1.33 mol / L FA 0.85 MA 0.15 A PbI3 perovskite precursor solution, with concentrations based on lead content, specifically includes solutes formamidinium iodide (FAI), methylamine iodide (MAI), lead iodide (PbI2), and methylamine chloride (MACl), with molar amounts of 1.02 mmol, 0.18 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF were added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0056] Under ambient temperatures of 25℃ and relative humidity of 30%, a prepared perovskite precursor solution was spin-coated onto the electron transport layer using a spin coater (KW-4A benchtop spin coater) at a speed of 3000 rpm for 6 seconds. Immediately afterwards, the layer was placed in a low-pressure auxiliary system (DL-10A quartz vacuum gauge and vacuum pump) for 30 seconds at a vacuum level of 10 Pa to allow rapid solvent evaporation, resulting in a well-crystallized mesophase film. After the low-pressure treatment, the film was annealed at 150℃ for 20 minutes to obtain a three-dimensional perovskite precursor solution. 0.85 MA 0.15 PbI3 perovskite thin film. Its scanning electron micrograph is shown in the following image. Figure 6As shown, the grains are relatively large and uniform in size, with no obvious pores on the surface, indicating good crystallinity. The volume of the spin-coated perovskite precursor is 60 μL.

[0057] Step 4: Preparation of quasi-two-dimensional perovskite nanocrystalline layers:

[0058] Under ambient temperature of 25℃ and relative humidity of 30%, a spin coater was used to coat the three-dimensional perovskite layer FA. 0.85 MA 0.15 80 μL of 1 mg / mL CsPbBr3 nanocrystals were spin-coated onto PbI3 at 4000 rpm for 30 s, followed by annealing at 80 °C for 5 min to obtain three-dimensional FA. 0.85 MA 0.15 PbI3 / zero-dimensional CsPbBr3 nanocrystalline perovskite thin film. Its scanning electron micrograph is shown in the image below. Figure 7 As shown, white spots appear on the grain surface and at the grain boundaries, indicating that CsPbBr3 nanocrystals were successfully spin-coated onto the surface of the three-dimensional perovskite thin film. 0.85 MA 0.15 Ion diffusion occurs between the PbI3 three-dimensional perovskite surface and zero-dimensional CsPbBr3 nanocrystals to passivate surface defects. Then, 80 μL of a 1 mg / mL MeO-PEAI / isopropanol solution is spin-coated at 4000 rpm for 30 s, followed by annealing at 80°C for 3 min. The scanning electron micrograph of the thin film is shown below. Figure 8 As shown, most of the white spots disappeared, the roughness decreased, and a large number of lamellar materials appeared at the grains and grain boundaries. The zero-dimensional CsPbBr3 nanocrystals on the surface underwent an in-situ reaction with MeO-PEA to form quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 perovskite nanocrystals, resulting in three-dimensional FA. 0.85 MA 0.15 PbI3 / (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 perovskite nanocrystalline layer.

[0059] In this embodiment, the three-dimensional FA 0.85 MA 0.15 The thickness of the PbI3 perovskite layer is 450 nm, and the thickness of the quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 perovskite nanocrystalline layer is 20 nm.

[0060] In this embodiment, zero-dimensional CsPbBr3 nanocrystals were synthesized using a hot-injection method. Specifically, 101.7 mg of cesium carbonate (Cs₂CO₃) was placed in a three-necked flask, along with 5 mL of octadecene (ODE) and 0.625 mL of oleic acid (OA). The mixture was heated and stirred at 120°C under vacuum for 30 min to generate a cesium oleate precursor solution. Then, 138.0 mg of lead bromide (PbBr₂) was placed in another three-necked flask, along with 10 mL of octadecene, 1 mL of oleic acid, and 1 mL of oleylamine (OAm). The mixture was heated and stirred at 120°C under vacuum for 30 min to form a lead bromide precursor solution. Both flasks were then purged with nitrogen and stored in a nitrogen atmosphere. The lead bromide precursor solution was heated to 170°C, and 1 mL of the cesium oleate precursor solution was rapidly injected into the lead bromide precursor solution. The mixture was stirred rapidly for 5 s and then cooled to room temperature in an ice bath to obtain the CsPbBr₃ nanocrystal stock solution. Methyl acetate (MAC) was added to the CsPbBr3 nanocrystal stock solution at a volume ratio of 1:3 for washing. After centrifugation at 8000 rpm for 5 min, the precipitate was retained. The precipitate was dispersed with n-hexane, and then an equal volume of MAC was added for a second washing. After centrifugation at 12000 rpm for 10 min, the precipitate was retained. The precipitate was dispersed again with n-hexane to obtain zero-dimensional CsPbBr3 nanocrystal colloids.

[0061] Step 5: Fabrication of the hole transport layer Spiro-OMeTAD:

[0062] Prepare a Spiro-OMeTAD precursor solution for the hole transport layer, specifically by adding 72.3 mg of solute Spiro-OMeTAD, followed by 1 mL of solvent chlorobenzene (CB), 28.8 μL of 4-tert-butylpyridine (tBP), and 17.5 μL of Li-TFSI (520 mg / mL).

[0063] Spiro-OMeTAD precursor solution for hole transport layer was spin-coated onto a perovskite layer. The spin-coating volume was 60 μL, the spin-coating speed was 4000 rpm, and the spin-coating time was 30 s. The thickness of the resulting hole transport layer was 150 nm.

[0064] Step 6: Fabrication of gold electrodes:

[0065] Gold electrodes were fabricated on the hole transport layer using vacuum evaporation at a vacuum level of 5 × 10⁻⁶. -4 Pa has an evaporation rate of 0.01-0.08 nm / s and a thickness of approximately 50 nm.

[0066] The transmission electron microscopy image of the zero-dimensional CsPbBr3 nanocrystals used in this embodiment is as follows: Figure 2As shown, the nanocrystals exhibit relatively uniform size and good dispersion. Transmission electron microscopy images of quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystals are shown below. Figure 4 As shown, compared to zero-dimensional CsPbBr3 nanocrystals, its morphology is plate-like. Figure 3 The image shows a high-resolution transmission electron microscopy image of zero-dimensional CsPbBr3 nanocrystals. The interplanar spacing of the (200) crystal plane is... High-resolution transmission electron microscopy images of quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystals, such as Figure 5 As shown, the interplanar spacing of its (200) crystal plane is Compared to CsPbBr3 nanocrystals, the interplanar spacing of this nanocrystal has changed significantly. This is because, at the microscopic level, the structure of the zero-dimensional perovskite nanocrystal has been altered. Ions diffuse into the lattice, creating a structure where two dimensions have similar (or identical) properties, while the other dimension exhibits significantly different properties due to the increased interplanar spacing. Therefore, this quasi-two-dimensional perovskite nanocrystal is a further structural modification of the zero-dimensional perovskite nanocrystal, resulting in a quasi-two-dimensional layered nanocrystal structure in zero dimensions.

[0067] In this embodiment, a solar simulator (EASISOLAR-50-3A) using a xenon lamp source to simulate sunlight was used to test the device's current-voltage (JV) characteristic curve, with a calibration light intensity of 100 mW / cm². 2 The test data was recorded using a digital source table (K-2400). The JV curve of the fabricated device is shown below. Figure 11 As shown, its open-circuit voltage is 1.14V and its current density is 25.57mA / cm². 2 The fill factor is 79.8%, and the photoelectric conversion efficiency is 23.26%.

[0068] Example 2.

[0069] Perovskite solar cells based on three-dimensional FAPbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0070] The other steps are the same as in Example 1, except that:

[0071] In step three, the three-dimensional perovskite layer is FAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes formamidinium iodide, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0072] Example 3.

[0073] Perovskite solar cells based on three-dimensional MAPbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0074] The other steps are the same as in Example 1, except that:

[0075] In step three, the three-dimensional perovskite layer is MAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes methylamine iodine, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0076] Example 4.

[0077] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (MeO-PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0078] The other steps are the same as in Example 1, except that:

[0079] The preparation of the three-dimensional perovskite layer in step three employs an anti-solvent method. Under ambient temperatures of 25°C and relative humidity of 30%, a spin coater is used to spin-coat the prepared perovskite precursor solution onto the electron transport layer. The spin coating is performed in two steps: first, a low-speed spin coating at 1000 rpm for 6 seconds, followed by a high-speed spin coating at 4000 rpm for 30 seconds. During the 20-second high-speed spin coating, 200 μL of chlorobenzene is rapidly added dropwise. After spin coating is complete, the layer is annealed at 150°C for 20 minutes to obtain well-crystallized three-dimensional perovskite. 0.85 MA 0.15 PbI3 perovskite thin films.

[0080] Example 5.

[0081] Based on 3D FA 0.85 MA0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (MeO-PEA2PbI2Cl2)(Cs2PbI2Cl2)5(CsPbCl3)5 nanocrystalline perovskite layers.

[0082] The other steps are the same as in Example 1, except that:

[0083] The perovskite nanocrystals in step four are CsPbCl3 with a concentration of 1 mg / mL. The preparation method is the same as that for CsPbBr3, except that 138.0 mg of lead bromide is replaced with 104.6 mg of lead chloride (PbCl2).

[0084] Example 6.

[0085] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (PEA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0086] The other steps are the same as in Example 1, except that:

[0087] The macromolecular organic halide amine salt in step four is PEAI, with a concentration of 1 mg / mL.

[0088] Example 7.

[0089] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (EA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0090] The other steps are the same as in Example 1, except that:

[0091] The macromolecular organic halide amine salt in step four is EAI, with a concentration of 1 mg / mL.

[0092] Example 8.

[0093] Perovskite solar cells based on three-dimensional FAPbI3 / quasi-two-dimensional (EA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0094] The other steps are the same as in Example 1, except that:

[0095] In step three, the three-dimensional perovskite layer is FAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes formamidinium iodide, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0096] The macromolecular organic halide amine salt in step four is EAI, with a concentration of 1 mg / mL.

[0097] Example 9.

[0098] Perovskite solar cells based on three-dimensional MAPbI3 / quasi-two-dimensional (EA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0099] The other steps are the same as in Example 1, except that:

[0100] In step three, the three-dimensional perovskite layer is MAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes methylamine iodine, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0101] The macromolecular organic halide amine salt in step four is EAI, with a concentration of 1 mg / mL.

[0102] Example 10.

[0103] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (EA2PbI2Cl2)(Cs2PbI2Cl2)5(CsPbCl3)5 perovskite nanocrystalline layers.

[0104] The other steps are the same as in Example 1, except that:

[0105] The perovskite nanocrystals in step four are CsPbCl3 with a concentration of 1 mg / mL. The preparation method is the same as that for CsPbBr3, except that 138.0 mg of lead bromide is replaced with 104.6 mg of lead chloride.

[0106] The macromolecular organic halide amine salt in step four is EAI, with a concentration of 1 mg / mL.

[0107] Example 11.

[0108] Based on 3D FA0.85 MA 0.15 Perovskite solar cells with PbI3 / quasi-two-dimensional (BA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0109] The other steps are the same as in Example 1, except that:

[0110] The macromolecular organic halide amine salt in step four is BAI, with a concentration of 1 mg / mL.

[0111] Example 12.

[0112] Perovskite solar cells based on three-dimensional FAPbI3 / quasi-two-dimensional (BA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite layers.

[0113] The other steps are the same as in Example 1, except that:

[0114] In step three, the three-dimensional perovskite layer is FAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes formamidinium iodide, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0115] The macromolecular organic halide amine salt in step four is BAI, with a concentration of 1 mg / mL.

[0116] Example 13.

[0117] Perovskite solar cells based on three-dimensional MAPbI3 / quasi-two-dimensional (BA2PbI2Br2)(Cs2PbI2Br2)5(CsPbBr3)5 nanocrystalline perovskite active layers.

[0118] The other steps are the same as in Example 1, except that:

[0119] In step three, the three-dimensional perovskite layer is MAPbI3 with a concentration of 1.33 mol / L. This concentration is based on the lead content and specifically includes solutes methylamine iodine, lead iodide, and methylamine chloride, with molar amounts of 1.2 mmol, 1.2 mmol, and 0.18 mmol, respectively. 100 μL of NMP and 800 μL of DMF are added sequentially as solvents to obtain a 900 μL perovskite precursor solution.

[0120] The macromolecular organic halide amine salt in step four is BAI, with a concentration of 1 mg / mL.

[0121] Comparative Example 1.

[0122] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 perovskite active layer.

[0123] The other steps are the same as in Example 1, except that:

[0124] Step four is not included in the fabrication process of perovskite solar cells.

[0125] The JV curve of the fabricated device is as follows: Figure 9 As shown, its open-circuit voltage is 1.08V and its current density is 25.52mA / cm². 2 The fill factor is 77.4%, and the photoelectric conversion efficiency is 21.33%.

[0126] Comparative Example 2.

[0127] Based on 3D FA 0.85 MA 0.15 Perovskite solar cells with PbI3 / zero-dimensional CsPbBr3 nanocrystalline perovskite active layer.

[0128] The other steps are the same as in Example 1, except that:

[0129] Step four involves spin-coating only CsPbBr3 nanocrystals with a concentration of 1 mg / ml, without spin-coating the subsequent MeO-PEAI / isopropanol solution.

[0130] The JV curve of the fabricated device is as follows: Figure 10 As shown, its open-circuit voltage is 1.13V and its current density is 25.49mA / cm². 2 The zero-dimensional CsPbBr3 nanocrystals, with a fill factor of 78.2% and a photoelectric conversion efficiency of 22.52%, can passivate surface defects in three-dimensional perovskites, improve interfacial contact, and thus increase the open-circuit voltage and fill factor, raising the photoelectric conversion efficiency from 21.33% to 22.52%. However, the presence of organic ligands during the synthesis of CsPbBr3 nanocrystals hinders electron transport, resulting in a decrease in current density.

[0131] Through the above examples and comparative illustrations, it is demonstrated that modifying three-dimensional perovskites with quasi-two-dimensional perovskite nanocrystals can significantly reduce the defect state density of the three-dimensional perovskite light-absorbing layer, improve the interfacial contact and energy level matching between the perovskite light-absorbing layer and the electron transport layer, and reduce nonradiative recombination. Devices fabricated using quasi-two-dimensional perovskite nanocrystals to modify three-dimensional perovskites exhibit optimized overall carrier transport performance and improved photoelectric conversion efficiency, showing promising application prospects in the photovoltaic field.

[0132] This invention is not limited to the embodiments described above, and variations can be made within the scope of the claims. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection of this invention is defined by the appended claims and their equivalents.

[0133] Matters not covered in this invention are common knowledge.

Claims

1. A quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell, characterized in that... It includes a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light-absorbing layer, a quasi-two-dimensional perovskite nanocrystal layer, a hole transport layer, and electrodes; The three-dimensional perovskite light-absorbing layer material is APbX3, where A is a formamidinium cation (FA). + ), methylamine cation (MA) + ) and cesium ions (Cs + One or more of the following; the X position is one or more of chloride ion, bromide ion, and iodide ion; The quasi-two-dimensional perovskite nanocrystal structure has the formula (B2PbX4). k (A2PbX4) m (APbX3) n Where k is 0~1, m and n are 0~20, A is a monovalent cation, B is a macromolecular organic halide amine salt cation, and X is one or more of monovalent halogen or pseudohalogen anions. The thickness of the three-dimensional perovskite is 200~1000nm, and the thickness of the quasi-two-dimensional perovskite nanocrystals is 0.1~100nm. The macromolecular organic halide amine salt cation B is specifically: methoxyphenethylamine ion (MeOPEA) + ), phenylethylamine ion (PEA) + pF-PEA ions + ), dimethylamine ion (DMA) + ), ethylamine ion (EA) + ), diethylamine ion (DEA) + ), mercaptoethylamine ion (ESA) + ), ethanolamine ions (EOA) + ), propylamine ion (PA) + ), butylamine ion (BA + ), isobutylamine ion (iBA) + ), phenylamine ion (PhA) + ), pyridine methylamine ion (PyA) + ), trifluoroethylamine ion (F3-EA) + ), trifluoromethylphenylethylamine ion (CF3-PEA) + ), trifluoromethylaniline ion (CF3-PhA) + ), trifluoromethylbenzamine ion (CF3-PMA) + ), 3-Dimethylamino-1-propylamine ion (3-Me2-PDA) + ), benzylamine ion (PMA) + ), phenylpropylamine ion (PPA) + ), phenylbutylamine ion (PhBA) + p-fluorobenzamide ions (pF-PMA) + ), 4-tert-butylbenzylamine ion (tBBA) + ), 4-tert-butylaniline ion (tBPA) + One or more of the following; The method for preparing the quasi-two-dimensional perovskite nanocrystal layer includes the following steps: spin-coating a zero-dimensional perovskite nanocrystal colloid onto a three-dimensional perovskite and annealing it at 20–150°C for 30–20 min; then spin-coating a layer of macromolecular organic halide amine salt solution and annealing it at 20–150°C for 30–20 min. The concentration of the zero-dimensional perovskite nanocrystal colloid is 0.1–20 mg / mL; the concentration of the macromolecular organic halide amine salt solution is 0.1–20 mg / mL, and the solvent is isopropanol.

2. The quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell as described in claim 1, characterized in that: The substrate is one of the following: fluorine-doped SnO2 conductive glass (FTO), indium tin oxide transparent conductive film glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate). The electrode is at least one of gold, silver, copper, aluminum, and carbon; The electron transport layer comprises at least one of tin dioxide, titanium dioxide, zinc oxide, methyl [6,6]-phenyl C61 butyrate (PCBM), and C60. The hole transport layer is composed of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), molybdenum trioxide (MoO3), and nickel oxide (NiO). x One or more of the following: cuprous iodide (CuI), cuprous thiocyanate (CuSCN), copper titanate (CuPc), and chromium oxide (Cr2O3); The electron transport layer has a thickness of 1~200nm, the hole transport layer has a thickness of 5~300nm, and the electrode has a thickness of 20~00nm.

3. The method for preparing a quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell as described in claim 1. Its characteristic is that the method includes the following steps: 1) An electron transport layer is fabricated on a cleaned transparent conductive substrate; 2) Fabrication of a three-dimensional perovskite layer on the electron transport layer; 3) Preparation of quasi-two-dimensional perovskite nanocrystal layer: Zero-dimensional perovskite nanocrystal colloid is spin-coated onto three-dimensional perovskite and annealed at 20-150℃ for 30s-20min; then, a layer of macromolecular organic halide amine salt solution is spin-coated and annealed at 20-150℃ for 30s-20min. The concentration of the zero-dimensional perovskite nanocrystal colloid is 0.1–20 mg / mL; the concentration of the macromolecular organic halide amine salt solution is 0.1–20 mg / mL, and the solvent is isopropanol. The macromolecular organohalogenated amine salts mentioned are: methoxyphenylethyl iodide (MeOPEAI), phenylethyl iodide (PEAI), p-fluorophenylethylamine iodide (pF-PEAI), dimethylamine hydroiodide (DMAI), ethyl iodide (EAI), diethylamine hydroiodide (DEAI), mercaptoethylamine hydroiodide (ESAI), ethanolamine iodide (EOAI), propylamine iodide (PAI), butylamine iodide (BAI), isobutylamine iodide (iBAI), phenylamine iodide (PhAI), pyridine methylamine iodide (PyAI), trifluoroacetyl iodide, etc. One or more of the following: aminoiodine (F3-EAI), trifluoromethylphenethylamine iodine (CF3-PEAI), trifluoromethylaniline iodine (CF3-PhAI), trifluoromethylaniline iodine (CF3-PMAI), 3-dimethylamino-1-propylamine iodine (3-Me2-PDAI), benzyl iodide (PMAI), phenylpropyl iodide (PPAI), phenylbutyl iodide (PhBAI), p-fluoroaniline iodine (pF-PMAI), 4-tert-butylaniline iodine (tBBAI), and 4-tert-butylaniline iodine (tBPAI); 4) Spin-coating hole transport material onto the perovskite layer at a concentration of 1–100 mg / mL; 5) Prepare metal electrodes on the hole transport layer by vacuum evaporation or carbon electrodes by blade coating.

4. The method for preparing a quasi-two-dimensional perovskite nanocrystal-modified three-dimensional perovskite solar cell as described in claim 3, characterized in that the preparation of the three-dimensional perovskite thin film in step 2) is one of the following two methods: Method 1: A three-dimensional perovskite light-absorbing layer is prepared by vacuum flash evaporation at an ambient temperature of 1–50℃ and a relative humidity of 2%–60%. A prepared perovskite precursor solution with a concentration of 0.5–2 mol / L is spin-coated onto the electron transport layer at a spin coating speed of 1000–6000 rpm for 5–60 s. Then, a low-pressure assisted treatment is performed at a pressure of 1–200 Pa for 10–120 s, followed by annealing at a temperature of 50–150℃ for 30 s–50 min to form the three-dimensional perovskite layer. Alternatively, in method two, a three-dimensional perovskite light-absorbing layer is prepared by a one-step spin coating method at an ambient temperature of 1–50℃ and an ambient relative humidity of 2%–60%. A prepared perovskite precursor solution with a concentration of 0.5–2 mol / L is spin-coated onto the electron transport layer. The spin coating equipment is operated at a speed of 1000–6000 rpm for 5–60 s. An anti-solvent is added dropwise during the spin coating process, followed by annealing at a temperature of 50–150℃ for 30 s–50 min to form a three-dimensional perovskite layer.

5. The method for preparing a quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell as described in claim 4, characterized in that the solvent of the perovskite precursor solution is one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile (ACN), dimethylacetamide (DMAc), γ-butyrolactone, methylamine formate, methylamine acetate, methylamine butyrate, and methanol.

6. The method for preparing a quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell as described in claim 3, characterized in that the spin coating speed in step 3) is 500-6000 rpm, the spin coating time is 5-120 s, the ambient temperature is 1-50℃, and the ambient relative humidity is 2%-60%.

Citation Information

Patent Citations

  • Method for preparing perovskite solar cell based on synergistic effect of CsPbX3 nano-crystals

    CN109360893A

  • Solar cell based on quasi two-dimensional-two-dimensional perovskite and preparation method thereof

    CN114824092A